Decreased expression of let-7c is associated with non-response of muscle-invasive bladder cancer patients to neoadjuvant chemotherapy - Vinall, Ruth L. (Genes Cancer, 2016)
The identification and development of biomarkers which predict response of muscle invasive bladder cancer (MIBC) patients to neoadjuvant chemotherapy would likely increase usage of this treatment option and thereby improve patient survival rates. MiRNA array and qRT-PCR validation was used to identify miRNA which are associated with response to neoadjuvant chemotherapy. RNA was extracted from a total of 41 archival, fully annotated, MIBC patient diagnostic biopsies (20 chemo-responders and 21 non-responders (response is defined as > 5 year survival rate and being pT0 post-chemotherapy)). Microarray and qPCR identified let-7c as being differentially expressed in chemo-responder versus non-responder patients. Patients with higher let-7c expression levels had significantly higher odds of responding to chemotherapy (p = 0.023, OR 2.493, 95% CI 1.121, 5.546), and assessment of let-7c levels allowed for prediction of patient response (AUC 0.72, positive predictive value 59%). Decreased let-7c was associated with MIBC incidence (p < 0.001), and significantly correlated with other related miRNA including those that were not differentially expressed between responders and non-responders. The combined data indicate let-7c plays a role in mediating chemoresistance to neoadjuvant chemotherapy in MIBC patients, and is a modest, yet clinically meaningful, predictor of patient response.